2017
DOI: 10.1021/acschemneuro.7b00121
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis Reveals the Identity of Aβ-Metal Complex Responsible for the Initial Aggregation of Aβ in the Synapse

Abstract: The mechanism of Aβ aggregation in the absence of metal ions is well established, yet the role that Zn2+ and Cu2+, the two most studied metal ions, released during neurotransmission, paly in promoting Aβ aggregation in the vicinity of neuronal synapses remains elusive. Here we report the kinetics of Zn2+ binding to Aβ and Zn2+/Cu2+ binding to Aβ-Cu to form ternary complexes under near physiological conditions (nM Aβ, μM metal ions). We find that these reactions are several orders of magnitude slower than Cu2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 65 publications
(149 reference statements)
0
21
0
Order By: Relevance
“…The metal ions released during synaptic transmission can induce amyloid-beta oligomer formation in the curved membrane of synapses. Through a combination of experimental kinetics studies and coupled reaction-diffusion simulations, we predicted that Cu (II) rather than Zn (II) plays an important role in the very early stages of Aβ aggregation in the synapse 53 . In addition, curved structures could also take place on cell debris.…”
Section: Discussionmentioning
confidence: 99%
“…The metal ions released during synaptic transmission can induce amyloid-beta oligomer formation in the curved membrane of synapses. Through a combination of experimental kinetics studies and coupled reaction-diffusion simulations, we predicted that Cu (II) rather than Zn (II) plays an important role in the very early stages of Aβ aggregation in the synapse 53 . In addition, curved structures could also take place on cell debris.…”
Section: Discussionmentioning
confidence: 99%
“…Research of the past two decades has led to a much improved understanding of the mechanisms of metal ion binding by Aβ peptides . There is a fundamental difference between the mechanism of metal ion binding by Aβ and that of the well‐structured metalloproteins .…”
Section: Metal Ionsmentioning
confidence: 99%
“…As discussed earlier, the basic phases of fibril formation are nucleation and fibril elongation or growth. In addition, once fibrils form, fragmentation, secondary nucleation, and fibril dissolution add greater complexity to the overall kinetics . Metal could affect any of these stages, though in different ways.…”
Section: Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data have been obtained previously for Cu II Ab 1Àx complexes. [15][16][17] Here, we studied the reaction mechanism for Cu II binding to the model peptide Ab 4-16 and found that the reaction follows a hierarchical fashion, going through two intermediate states and then reaching the final tight complex.…”
mentioning
confidence: 99%